THE PECULIARITY OF THE VALUE ORIENTATIONS OF MODERN PRESCHOOLERS - Dombek, Svetlana; Lebedeva, Natalia; Michailova, Arina; Pradun, Inna; Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the problem of value orientations of modern preschoolers. The authors clarify the concepts of «value», «value orientations», define the place of value orientations in the structure of the personality of a preschooler, the role of the teacher in the development of the value system of children.The article describes the empirical study of the value orientations of children of senior preschool age: diagnostic tools are characterized, the procedure of diagnosing is described, and the results are analyzed. The authors indicate the trends in the change of value orientations of children, infer which value orientations are dominate and typical for modern elder preschoolers.The article is intended for public reading and for those who are interested in pedagogical research.